Modelling Zakat distribution for enhancement human capital development / Hazlina Abdul Halim … [et_al.] - Abdul Halim, Hazlina; Said, Jamaliah; Syed Yusuf, Sharifah Norzehan; Bahrom, Hasan (Research Management Institute (RMI), 2012)
One of the functions of business development program of Selangor Zakat Board is creation a business enterprise among Asnafs. As such “Asnaf Entrepreneurial Program” was launched in 2003 to facilitate rightful Asnafs to starts business and eventually able to generate stable income to above poverty line through initial business capital assistance. This program is developing through the Economics Development Department of SZB by providing continuous support to rightful Asnafs to elevate their living standards through business activities such as “my burger” and “Asnaf market”. The aim of this program is to encourage asnafs to be self-sufficient. The initial business assistance provide by SZB to Asnafs are in various form ranging from equipment needed to start business to infrastructure such stalls, booth, workshop as well as financial assistance. The aim is to eventually train them so that they are able to won and operate the business independently. Importantly, the aim of this project is to provide adequate level of opportunities for the asnafs so that after certain period of financial assistance they are able to be financially independent. However, most of the capital assistance provide by Selangor Zakat Board ended in failure. Very few of the program participants have become successful entrepreneur. This study aims to provide understandings on the success of the capital assistance via the economic development programs from the Lembaga Zakat Selangor. This study also examined difference between successful male and female asnaf entrepreneurs in term of five core values of marketing strategy, product/service innovation, religious belief/practiced, entrepreneurial orientation and financial management. Based on 39 successful entrepreneurs the finding discovered that successful Asnaf entrepreneur possessed certain core value of personal qualities factors and skills like communication skills, self-reliance, ability to identify and exploit opportunities, innovative, creativity, willingness to take chances, even it means to expose oneself to risk.The finding also discovered that there are many differences successful male and female Asnaf entrepreneurs. Significant different between male and female successful asnaf entreprenuer were found in scores on product/services innovation, religious belief/practiced, relationship with customers and marketing technique.